EKSISTENSI MASYARAKAT PASCA PILAKADA PAMEKASAN 2018: Studi Perilaku Pemilih Masyarakat Desa Ponteh Kecamatan Galis Kabupaten Pamekasan melalui Pendekatan Sosiologi Agama - Mohammad Fahrur Rozi (STIU Al-Mujtama Pamekasan, 2019)
Abstrac: Behavior social of religious in society is a mirror can be describe a special characteristics or characteristics in a region and be differentiator between one region and the other. Then, Behavior is inseparable in daily life in society will have an impact to yourself, family, society and the environment. Islam is the religion of rahmatan lil amin alamin that teaches humans to interact based on the Qur'an and Hadith, so that can be occur a harmonious balance between hablu min Allah and hablu min al-Nass and can deliver an area to baldatun tayyibatun wa rabbun ghafur. Keywords: Behavior, social, of religious